Synthesis of 2,4-Disubstituted Imidazoles via Nucleophilic Catalysis - Shabalin, Dmitrii A.; Dunsford, Jay J.; Ngwerume, Simbarashe; Saunders, Alexandra R.; Gill, Duncan M.; Camp, Jason E. (Synlett, 2020)
A convergent, microwave-assisted protocol for the synthesis of disubstituted NH-imidazoles via nucleophilic catalysis is described. The substituted imidazoles are accessed via the intramolecular addition of a variety of amidoxime substrates to activated alkynes followed by a thermally induced rearrangement of the in situ generated O-vinylamidoxime species. The unprotected imidazoles contain an aryl group at the 2-position as well as an ester moiety at the 4-position.
Keywords: nucleophilic catalysis; imidazole; heterocycles; microwave; 19F NMR; rearrangement